2013
DOI: 10.1093/jrr/rrt080
|View full text |Cite
|
Sign up to set email alerts
|

Significance of low-dose radiation distribution in development of radiation pneumonitis after helical-tomotherapy-based hypofractionated radiotherapy for pulmonary metastases

Abstract: Hypofractionated radiotherapy (HRT) is now commonly used for pulmonary malignancies, since a tumoricidal dose can be accurately delivered to the target without a consequential dose to adjacent normal tissues. However, radiation pneumonitis (RP) is still a major problem after HRT. To determine the significant parameters associated with developing RP, we retrospectively investigated data from patients with lung metastases treated with HRT using helical tomotherapy. A total of 45 patients were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 18 publications
4
22
1
Order By: Relevance
“…27,28 When analyzing the predictive factors potentially involved in the development of RP, we could find neither dosimetric nor clinical factors significantly associated with treatment-related toxicity. In contrast to some other series employing HT in either a conventional or a hypofractionated schedule for primary and metastatic lung tumours, where cutoff values for ipsilateral 29 and contralateral percentage of lung volume receiving 5 Gy 11,30 have been proposed, these findings confirm our previous experience with HHT on a limited cohort of patients with early-stage NSCLC. 31 Fourth, we provided a detailed radiological description of lung appearances after HHT and concluded that a specific pattern of lung injury was not associated with this technique.…”
Section: Discussionsupporting
confidence: 86%
“…27,28 When analyzing the predictive factors potentially involved in the development of RP, we could find neither dosimetric nor clinical factors significantly associated with treatment-related toxicity. In contrast to some other series employing HT in either a conventional or a hypofractionated schedule for primary and metastatic lung tumours, where cutoff values for ipsilateral 29 and contralateral percentage of lung volume receiving 5 Gy 11,30 have been proposed, these findings confirm our previous experience with HHT on a limited cohort of patients with early-stage NSCLC. 31 Fourth, we provided a detailed radiological description of lung appearances after HHT and concluded that a specific pattern of lung injury was not associated with this technique.…”
Section: Discussionsupporting
confidence: 86%
“…The reported lung doses are well below the suggested QUANTEC constraints [37] and the V5 constraint proposed by Jo et al to limit the risk of radiation pneumonitis [38]. We also note that the contralateral lung receives less dose in prone than in supine position.…”
Section: Discussionsupporting
confidence: 59%
“…There is a similar risk pattern for radiation-induced pneumonitis. Although the data in breast cancer patients are limited (22), several authors have found low-dose lung parameters, including the volume receiving 10 Gy (V10) and 5 Gy (V5), to be significant predictors in patients treated for breast and lung cancer (2325). …”
Section: Discussionmentioning
confidence: 99%